Real exchange rate misalignment and economic growth: An empirical analysis for Ethiopia - Alemnew, Teklebirhan; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2024)
In both developing and developed economies, academic and policy discussions have consistently emphasized that achieving stable economic growth and maintaining internal and external balance require an exchange rate aligned with its long-term equilibrium value. This paper examines the impact of real exchange rate misalignment on Ethiopia's economic growth from 1980 to 2022. The study begins by estimating the equilibrium real exchange rate using the Behavioral Equilibrium Exchange Rate (BEER) approach to calculate the misalignments. It then analyzes the effects of these misalignments on economic growth using Vector Autoregressive (VAR) and Hansen's (2000) threshold regression model. The VAR and Impulse Response Function (IRF) analyses reveal that real exchange rate misalignments have an immediate positive impact on economic growth, which diminishes between the eighth and sixteenth years and stabilizes as a permanent long-term effect. The threshold regression results indicate that undervaluation of the Ethiopian Birr enhances economic growth up to a 13.95% deviation from the equilibrium real exchange rate, while overvaluation supports growth up to a 7.15% threshold. Beyond these limits, misalignments hinder growth. The study underscores the importance of avoiding excessive deviations from the equilibrium exchange rate to sustain economic growth. Furthermore, it highlights the need for consistent macroeconomic policies to minimize the gap between the actual and equilibrium real exchange rates. These findings emphasize the critical role of exchange rate policy in promoting sustainable economic development in Ethiopia.